Adaptación a los impactos del cambio climático de sistemas agrícolas basados en papa del altiplano boliviano - Carlos Eduardo Quezada Lambertin (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2021)
– Potato is one of the most important crops for food security in Bolivia. In the Bolivian Altiplano, most of the agricultural systems are based on this crop. However, national yields are the lowest in the region (5.7 Tn ha-1 ), and agricultural systems are highly vulnerable to the impacts of climate change. This situation may be worse in future climate scenarios. The aim of this study is to evaluate the potato production adaptation to climate change under the most pessimistic climate scenario in the year 2050 using three adaptation strategies: management of the agricultural calendar, management of biological diversity, and application of complementary irrigation. For this purpose, the APEX crop simulation model is used to simulate potato growth and yield under the Representative Concentration Path (RCP) 8.5 scenario in the Patacamaya community (Bolivian Central Altiplano). The results show a significant increase in potato yields for each adaptation measure, and when the three strategies are combined, the effectiveness to reduce the impacts of climate change increases, and consequently, productive yields increase by 48% (46 Tn ha-1 ), and potato-based systems resilience is improved.
Keywords: Q01; Q19; Q24; Q25; 330; Potato production; adaptation to climate change; simulation models; Bolivian highlands